Utilização de glicerina e capulho de algodão em suplementos para bovinos de corte em pastejo - José Neto, Antônio (2012)
This dissertation was prepared from the results of four experiments that assessed the performance and the nutritional characteristics of Nellore cattle under grazing, supplemented with glycerol and bolls of cotton, in two seasons. The first experiment was conducted to evaluate levels of roughage supplementation with cotton bolls in the body weight of cattle grazing in the transition period dry water on nutritional animal. We used five Nellore steers, not bulls, age and initial body weight average of 22 months and 392 kg. The experimental area consisted of five paddocks of 0.24 ha formed with Brachiaria brizantha cv. Marandu with forage mass (FM) and potentially digestible dry matter (MSPD) of 1837.91 and 1080.71 kg DM/ha, respectively. The experimental design was structured in 5 x 5 Latin square design with five experimental periods of 17 days, in which the levels of roughage supplementation with cotton boll as a function of body weight (BW) cattle, evaluated in terms of intake and digestibility of nutrients, ammonia nitrogen (NH3-N) and pH were: Cap1 - 3.6; Cap2 - 4.9; Cap3 - 6.1 and Cap4 - 7.3 g / kg of the average PC. The roughage supplementation was given daily at 10 am with the respective amounts: Cap1 - 1.5; Cap2 - 2.0; Cap3 - 2.5 and Cap4 - 3.0 kg/animal and control animals were supplemented only with mineral mixture (ad libitum). No effect of supplementation strategies (P>0.10) in relation to consumption of dry matter and nutrients. There was no difference in the values of DM, OM, CP, NDF, NFC and CT, however, significant variation (P<0.10) for EE. At time 0 hours, the pH of animals supplemented with 6.1 and 7.3 g / kg body weight differ (P<0.10) compared to control group. Already at the time 4 hours, there was no difference between supplements (P>0.10). There was no difference (P>0.10) for the values of NH3-N at time 0 hours. Difference (P<0.10) values for the N-NH3 4 hours time, with the highest concentration of N-NH3 to the level of 4.9 g/kg BW. The second experiment was conducted to evaluate levels of roughage supplementation with cotton bolls in the body weight of cattle grazing in the transition period dry water on performance and cost. We used 20 Nelore steers, not bulls, age and initial body weight average of 22 months and 366 kg. The experimental area consisted of four plots of 1.6 ha formed with Brachiaria brizantha cv. Marandu with forage mass (FM) for 1966.87 and potentially digestible dry matter (MSPD) of 1147.32 kg DM/ha. The experiment was structured in a completely randomized design (CRD) in the levels of roughage supplementation with cotton boll as a function of body weight (BW) cattle, judged on the total weight gain (TWG), average daily gain (GMD) and the economic analysis were: Cap1 - 3.6; Cap2- 4.9 and Cap3 - 6.1 g / kg of the average PC. The roughage supplementation was given daily at 10 am with the respective amounts: Cap1 - 1.5; Cap2 - 2.0 and Cap3 - 2.5 kg/animal and control animals were supplemented only with mineral mixture (ad libitum). There were differences (P<0.10) between the levels of supplementation and the control group on average daily gain of animals, the level of 4.9 g/kg body weight which provided better performance. As for the economic evaluation, we observed a higher return for the supplementation level of 4.9 g/kg body weight. The third experiment was conducted to evaluate the effect of protein sources and nitrogen associated with the residual biodiesel glycerin in the diet of beef cattle grazing in the rainy season on nutritional parameters. We used five Nellore steers, not bulls, age and initial body weight average of 25 months and 448.2 kg. The experimental area consisted of five paddocks of 0.24 ha each formed with Brachiaria brizantha cv. Marandu, with a mass of forage (MF) and potentially digestible dry matter (MSPD) of 1679.50 and 1139.29 kg/ha of DM, respectively. The experimental design was structured in 5 x 5 Latin square design with five experimental periods of 17 days to assess the following supplements: control (only mineral); GU - glycerin with urea; GFS - glycerol with soybean meal; GFA - Glycerine with cottonseed meal and GGL - glycerin with corn gluten meal. The variables: intake and digestibility of nutrients, ammonia nitrogen (NH3-N) and pH. The supplementation was done daily at 10 a.m., with supply of 2.0 kg of supplement/animal. Control animals were supplemented only with mineral mixture (ad libitum). There was no difference (P>0.05) for the use of MST, MSF, MO, MOF, EE, NDF, TDN and CT. But there was no difference in CP intake (P = 0.0002) and CNF (P = 0.005) between the supplements. There were differences (P = 0.0057) for the values of CP digestibility. No significant difference (P>0.05) for ruminal pH values. The values of NH3-N, four hours after supplementation, we found a difference (P = 0.0438) between the animals that received multiple supplements in relation to control animals. At time 0 hours gave the highest value UG add N-NH3 (P = 0.0849) compared to GFA. The fourth experiment was conducted to evaluate the effect of protein sources and nitrogen associated with the residual biodiesel glycerin in the diet of beef cattle grazing in the rainy season on performance and cost. We used 20 Nelore steers, not bulls, age and initial body weight average of 25 months and 422 kg. The experimental area consisted of four plots of 1.6 ha each formed with Brachiaria brizantha cv. Marandu, with a mass of forage (MF) and potentially digestible dry matter (MSPD) of 1552.71 and 1146.01 kg/ha of DM, respectively. The experiment was structured in a completely randomized design to evaluate the following supplements: control (only mineral); GU - glycerin with urea; GFS - glycerol with soybean meal and GFA - glycerol with cottonseed meal. The variables: total weight gain (TWG), average daily gain (ADG), rate of fat accumulation (Tx.EG) and economic analysis. The supplementation was done daily at 10 am, with supply of 2.0 kg of supplement/animal. Control animals were supplemented only with mineral mixture (ad libitum). There was no difference (P>0.10) between the levels of supplementation and the control group on average daily gain of animals. As for the economic evaluation, the combination of glycerin with urea showed better economic performance. There was no difference (P>0.10) between the rate of accumulation in subcutaneous fat in the Longissimus dorsi (Tx.EGLG) and croup (Tx.EGP8) among experimental treatments.